Effect of Chitin and Chitooligosaccharide on In vitro Growth of Lactobacillus rhamnosus GG and Escherichia coli TG - Selenius O; Korpela J; Salminen S; Gallego CG (SHAHID BEHESHTI UNIV MEDICAL SCIENCES, FAC MED, 2025)
Background and Objective: Given the rising tendency of using insects as food, research regarding the food safety issues and health implications of edible insects are necessary. Insects have an external skeleton that is mainly composed of chitin-a nontoxic, fiber-like polysaccharide. Chitin and its derivative compounds can take part in maintaining healthy gut microbiota, by promoting or inhibiting the growth of several gut bacteria depending on the chitinous substrate. Healthy composition of gut microbiota can prevent intestinal disease states and food digestion problems. The aim of the study is to characterize the impact of chitin and chitooligosaccharides on the growth of two gut bacteria Lactobacillus rhamnosus GG and Escherichia coli TG, to provide further understanding on possible outcomes of consuming insects.Materials and Methods: Micro plate wells were prepared with tryptone soy broth in 0.5 and 0.1% wv(-1) chitin concentrations and in 0.5, 0.1, and 0.05% wv(-1) chitooligosaccharide concentrations. Bacteria were added and the growth parameters of Lactobacillus rhamnosus GG and Escherichia coli TG were obtained by measurement of optical density at 600 nm in 37 degrees C.Results and Conclusion: Chitooligosaccharides enhanced the growth of Lactobacillus rhamnosus GG and inhibited the growth of Escherichia coli TG in the lowest tested concentration of 0.05% wv(-1). Chitin completely inhibited the growth of both bacteria in the lowest tested concentration of 0.1% wv(-1). Chitooligosaccharides appear promising as potential prebiotic compounds associated with insect food products. Chitin has a strong antibacterial effect on tested bacteria. However, the In vitro results should be verified in well-designed human studies.